Aqueous Root Extract from Ononis spinosa Exerts Anti-adhesive Activity against Uropathogenic Escherichia coli - Deipenbrock, Melanie; Sendker, Jandirk; Hensel, Andreas (Planta Medica, 2020)
Extracts from Ononis spinosa are traditionally used for urinary tract infections due to diuretic and anti-inflammatory activity. A potential influence on the virulence of uropathogenic Escherichia coli has not been investigated until now. The following study aimed to investigate the influence of an aqueous O. spinosa extract on uropathogenic E. coli and uropathogenic E. coli host cell interaction. A hot water extract from the roots of O. spinosa (O. spinosa extract) was characterized by LC-qTOF-MS. The influence of O. spinosa extract on the proliferation of uropathogenic E. coli UTI89 and on cell viability against human T24 bladder cells was investigated. Anti-adhesive activity of O. spinosa extract was assessed by flow cytometry, evaluating the adhesion of fluorescent-labelled UTI89 to T24 bladder cells. Internalization of uropathogenic E. coli into T24 cells was monitored by an invasion assay. O. spinosa extract was characterized by the presence of isoflavones, isoflavanones, licoagrosides, pterocarpans, tartaric acid derivatives, and saponines. O. spinosa extract had no influence on the proliferation of uropathogenic E. coli (125 – 1000 µg/mL) and did not influence the cell viability of T24 cells. Bacterial adhesion to T24 cells was significantly (p > 0.001) inhibited by O. spinosa extract in a concentration-dependent manner (125 – 1000 µg/mL) during coincubation. Preincubation of uropathogenic E. coli or T24 cells with O. spinosa extract reduced bacterial adhesion, but to a lower extent than during coincubation. Consequently, the reduced bacterial adhesion also leads to a reduced internalization of uropathogenic E. coli uropathogenic E. coli into the host cell. O. spinosa extract does not interact with FimH-mediated uropathogenic E. coli adhesion to host cells. From these data, the traditional use of O. spinosa extracts for urinary tract infections seems to be rationalized.
Keywords: Ononis spinosa; Fabaceae; adhesion; urinary tract infections; uropathogenic E. coli